How Knowledge Sharing and Human Resource Management Affect How Well Employees Do Their Jobs - Adelmi Parera; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research explores how human resource management (HRM) and knowledge sharing affect employee performance in the Kurdistan Region. The literature review discusses the importance of HRM and Knowledge sharing for organizations and companies and their effects on employee performance. An investigation studied how HRM and knowledge sharing affect employee performance. A questionnaire was used to collect demographic data and assess the correlation between the two factors. The research methodology includes a quantitative approach with a survey of employees working in governmental and non-governmental organizations and companies. A total of 210 responses were collected through the questionnaire. We analyzed data using SPSS software to enhance HRM practices and promote knowledge sharing among employees, which resulted in improved performance. Using SPSS software, data was analyzed to improve HRM practices and encourage knowledge sharing among employees, ultimately leading to better performance.